2016
DOI: 10.5603/kp.a2015.0193
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fragmented QRS complex in myocardial scar detection: systematic review and meta-analysis of the literature

Abstract: A b s t r a c t Background and aim:The present study aimed to investigate the diagnostic value of fragmented QRS complex (fQRS) on 12-lead electrocardiogram (ECG) for myocardial scar detection, and presented the results in a systematic review and meta-analysis format.Methods: Medline, SCOPUS, and ISI Web of Knowledge were searched electronically with "Fragmented QRS" or "fQRS" as key words. All related studies that had evaluated the accuracy of fQRS for myocardial scar diagnosis were included.Results: Eight st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…For example, although pathologic Q-wave is known as the marker of myocardial infarction (MI) on a 12-lead EKG, its capacity in detecting myocardial scars is confined to only about one third of patients with documented MI [9,10]. It has been suggested that fQRS is more sensitive than Q-wave for identifying myocardial scars [11]. Also, an association between fQRS and regional and global LV dysfunction has been reported in patients with coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…For example, although pathologic Q-wave is known as the marker of myocardial infarction (MI) on a 12-lead EKG, its capacity in detecting myocardial scars is confined to only about one third of patients with documented MI [9,10]. It has been suggested that fQRS is more sensitive than Q-wave for identifying myocardial scars [11]. Also, an association between fQRS and regional and global LV dysfunction has been reported in patients with coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…The mean age was 39.5 years, and 37 (84.1%) of the participants were women. The median SLEDAI-2K was 13.5 (IQR, [10][11][12][13][14][15][16][17][18][19][20], and the median period from the estimated date of onset to the date of diagnosis was 3 months (IQR, 2-15). Twenty-six patients (59.1%) had fQRS at the time of diagnosis, 18 patients were followed, and 6 patients (33.3%) disappeared fQRS after immunosuppressive therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The fQRS may be caused by zigzag conductions around the myocardium previously scarred by ischemia or inflammation [12]. It is useful for identifying myocardial scars such as those resulting from CAD and cardiac sarcoidosis, for identifying high-risk patients with various cardiac diseases, and for predicting sudden cardiac death in the general population [11,[13][14][15][16][17]. The prevalence of fQRS appears to be higher in patients with rheumatic diseases, such as rheumatoid arthritis (RA), systemic sclerosis (SSc), ankylosing spondylitis, and Behçet's disease, than in controls, and similar findings have been reported in patients with SLE [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the presence of fQRS was found to be useful in detection of myocardial scar, 7 and in prediction of myocardial infarction and reperfusion parameters. 8 However, these studies were designed for fQRS in patients with narrow QRS.…”
Section: Introductionmentioning
confidence: 98%